Bone-Conducted oVEMP Latency Delays Assist in the Differential Diagnosis of Large Air-Conducted oVEMP Amplitudes - Taylor, Rachael L.; Magnussen, John S.; Kwok, Belinda; Young, Allison S.; Ihtijarevic, Berina; Argaet, Emma C.; Reid, Nicole; Rivas, Cheryl; Pogson, Jacob M.; Rosengren, Sally M.; Halmagyi, G. Michael; Welgampola, Miriam S. (Frontiers in Neurology, 2020)
Background: A sensitive test for Superior Semicircular Canal Dehiscence (SCD) is the air-conducted, ocular vestibular evoked myogenic potential (AC oVEMP). However, not all patients with large AC oVEMPs have SCD. This retrospective study sought to identify alternate diagnoses also producing enlarged AC oVEMPs and investigated bone-conducted (BC) oVEMP outcome measures that would help differentiate between these, and cases of SCD. Methods: We reviewed the clinical records and BC oVEMP results of 65 patients (86 ears) presenting with dizziness or balance problems who underwent CT imaging to investigate enlarged 105 dB nHL click AC oVEMP amplitudes. All patients were tested with BC oVEMPs using two different stimuli (1 ms square-wave pulse and 8 ms 125 Hz sine wave). Logistic regression and odds ratios were used to determine the efficacy of BC oVEMP amplitudes and latencies in differentiating between enlarged AC oVEMP amplitudes due to dehiscence from those with an alternate diagnosis. Results: Fifty-three ears (61.6%) with enlarged AC oVEMP amplitudes were identified as having frank dehiscence on imaging; 33 (38.4%) had alternate diagnoses that included thinning of the bone covering (near dehiscence, n = 13), vestibular migraine (n = 12 ears of 10 patients), enlarged vestibular aqueduct syndrome (n = 2) and other causes of recurrent episodic vertigo (n = 6). BC oVEMP amplitudes of dehiscent and non-dehiscent ears were not significantly different (p > 0.05); distributions of both groups overlapped with the range of healthy controls. There were significant differences in BC oVEMP latencies between dehiscent and non-dehiscent ears for both stimuli (p < 0.001). A prolonged n1 125 Hz latency (>11.5 ms) was the best predictor of dehiscence (odd ratio = 27.8; 95% CI:7.0-111.4); abnormal n1 latencies were identified in 79.2% of ears with dehiscence compared with 9.1% of ears without dehiscence. Conclusions: A two-step protocol of click AC oVEMP amplitudes and 125 Hz BC oVEMP latency measures optimizes the specificity of VEMP testing in SCD.